TO THE 100TH ANNIVERSARY OF THE NATIONAL ACADEMY OF SCIENCES OF UKRAINE – THE CRADLE OF DOMESTIC SCIENCE AND TECHNOLOGY - M. I. Baranov (National Technical University "Kharkiv Polytechnic Institute", 2018)
Purpose. Preparation of short scientifically-historical essay about creation and development of the National Academy of Sciences (NAS) of Ukraine. Methodology. Known scientific methods of collection, analysis and analytical treatment of scientific and technical information, touching creation and development of NAS of Ukraine and resulted in scientific monographs, journals and internet-reports. Results. A short scientifically-historical essay is presented about creation and development of NAS of Ukraine. The main scientific achievements of NAS of Ukraine in various fields of science are presented. It is pointed that a large scientifically-organizational contribution to these achievements brought by present President of NAS of Ukraine, Academician B.Ye. Paton, his 100th Birthday (27 November, 2018) coincides surprising appearance with the 100th anniversary of NAS of Ukraine. An important role of NAS of Ukraine in the development of society and international scientific and technical cooperation was noted. The results of scientific research, achieved over the past few years by the Institute of Technical Problems of Magnetism of the NAS of Ukraine (Kharkiv), as well as by the Institute of Ionosphere of the NAS and Departments of education and science (DES) of Ukraine (Kharkiv) are briefly presented. The research cooperation in the field of electrical engineering of NTU «KhPI» with scientific institutions of the NAS of Ukraine is highlighted. Originality. Certain systematization is executed of known from scientific journals and other mass of scientific and technical materials, touching the results of activity of research workers of institutes of NAS of Ukraine in the last few years. Practical value. Scientific popularization and deepening for the students of higher school, engineer-technical and scientific workers, working in the different sectors of economy of country, scientific and technical knowledge in an area of physical-technical and mathematical sciences, chemical and biological sciences, and also social and humanitarian sciences, extending their scientific range of interests and further development of scientific and technical progress in society.